"Eyewitnesses to a Tragedy": How the Collegian, the Student Newspaper of South Carolina State College, Covered the 1968 Orangeburg Massacre. Issue 1 (2nd January 2021) - Mozie, Dante E.
Abstract : On the night of February 8, 1968, in Orangeburg, South Carolina, a town located ninety minutes away from Charleston, state highway patrolmen were stationed at the edge of South Carolina State College, a historically black institution, hoping to gain control of a crowd of unarmed students protesting a nearby segregated bowling alley. Triggered by what they erroneously believed was gunfire aimed toward them, the patrolmen fired into the group, killing three young men and wounding twenty-eight others. Among those covering what became known as the Orangeburg massacre was the college's student newspaper, the Collegian . Textual analysis and media framing theory guide this examination of how the campus newspaper staff used their coverage to honor their fallen peers. Collegian coverage also communicated the anger of a campus community that felt betrayed by state lawmakers and expressed frustrations over what many believed was a lack of accurate news coverage by the mainstream media.